The dynamics identification of asynchronous electric drives via frequency response - Vladimir L. Kodkin; Aleksandr Sergeevich Anikin; Aleksandr A. Baldenkov (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
The article substantiates the necessity of identifying the dynamics of asynchronous electric drives with frequency control. It is proposed to use nonlinear transfer functions and the formula of a family of frequency responses of an electric drive, depending on the frequency of the stator voltage and slip. Experiments and simulations confirming theoretical conclusions are presented. The frequency responses of the drive of the stand calculated by the proposed method allowed to explain those problems of frequency control that were not explained by traditional methods - analytical, vector diagrams, substitution schemes, etc. This same technique allowed us to formulate a structural correction of the asynchronous electric drives. In contrast to the previously published research materials of asynchronous electric drives, a detailed qualitative analysis of the obtained nonlinear frequency responses and the interrelation of these characteristics with experimental results is shown for the first time in the article.